Disentangling the role of surface topography and intrinsic wettability in the prey capture mechanism of Nepenthes pitcher plants. (1st January 2021) - Labonte, David; Robinson, Adam; Bauer, Ulrike; Federle, Walter
Graphical abstract: Abstract: Nepenthes pitcher plants capture prey with leaves specialised as pitfall traps. Insects are trapped when they 'aquaplane' on the pitcher rim (peristome), a surface structured with macroscopic and microscopic radial ridges. What is the functional significance of this hierarchical surface topography? Here, we use insect pad friction measurements, photolithography, wetting experiments and physical modelling to demonstrate that the ridges enhance the trap's efficacy by satisfying two functional demands on prey capture: Macroscopic ridges restrict lateral but enhance radial spreading of water, thereby creating continuous slippery tracks which facilitate prey capture when little water is present. Microscopic ridges, in turn, ensure that the water film between insect pad and peristome remains stable, causing insects to aquaplane. In combination, the hierarchical ridge structure hence renders the peristome wettable, and water films continuous, so avoiding the need for a strongly hydrophilic surface chemistry, which would compromise resistance to desiccation and attract detrimental contamination.